Post-harvest technology and marketing of vegetables in the royal project foundation - D. Boonyakiat (2018)
Improvements in post-harvest technology and food safety in Thailand have been implemented for high-end markets such as supermarkets, hypermarkets and export markets. However, many domestic markets, especially in rural areas, have no requirement for high quality vegetables. Post-harvest handling for vegetables in this market is different. Post-harvest management, food safety and marketing of fresh vegetables in Thailand are discussed.